Changes in length of period of the spawning run for pacific salmons in the rivers in the north of Primorsky Territory - E. I. Barabanschikov (Известия ТИНРО)
Comparative data on changes in structure and length of the spawning run for chum salmon, cherry salmon and pink salmon in the rivers of the northern part of Primorsky Territory are presented for 1998–2022. Appearance of new seasonal groups is noted for all these species. Length of the periods of spawning has become longer.